ESPRAS Survey on Continuing Education in Plastic, Reconstructive and Aesthetic Surgery in Europe - Moellhoff, Nicholas; Arnez, Tine; Athanasopoulos, Elias; Costa, Horacio; De Santis, Giorgio; De Mortillet, Stephane; Demirdöver, Cenk; Benedetto, Giovanni di; Dzonov, Boro; Elander, Anna; Hansson, Emma; Henley, Mark; Jecan, Cristian Radu; Kaartinen, Ilkka; Karabeg, Reuf; Kharkov, Andrey; Kneafsey, Brian; Gjorgova, Smilja Tudzarova; Palencar, Drahomir; Portincasa, Aurelio; Psaras, Georgios; Rakhorst, Hinne; Alonso, Maria Elena Ruiz; Rouif, Michel; Saboye, Jacques; Pompeo, Fabio Santanelli di; Spendel, Stephan; Stepic, Nenad; Vasar, Olavi; Zic, Rado; Giunta, Riccardo E. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2022)
Background Specialty training in plastic, reconstructive and aesthetic surgery is a prerequisite for safe and effective provision of care. The aim of this study was to assess and portray similarities and differences in the continuing education and specialization in plastic surgery in Europe.Material and Methods A detailed questionnaire was designed and distributed utilizing an online survey administration software. Questions addressed core items regarding continuing education and specialization in plastic surgery in Europe. Participants were addressed directly via the European Leadership Forum (ELF) of the European Society of Plastic, Reconstructive and Aesthetic Surgery (ESPRAS). All participants had detailed knowledge of the organization and management of plastic surgical training in their respective country.Results The survey was completed by 29 participants from 23 European countries. During specialization, plastic surgeons in Europe are trained in advanced tissue transfer and repair and aesthetic principles in all parts of the human body and within several subspecialties. Moreover, rotations in intensive as well as emergency care are compulsory in most European countries. Board certification is only provided for surgeons who have had multiple years of training regulated by a national board, who provide evidence of individually performed operative procedures in several anatomical regions and subspecialties, and who pass a final oral and/or written examination.Conclusion Board certified plastic surgeons meet the highest degree of qualification, are trained in all parts of the body and in the management of complications. The standard of continuing education and qualification of European plastic surgeons is high, providing an excellent level of plastic surgical care throughout Europe.Hintergrund Die Facharzt-Weiterbildung für Plastische und Ästhetische Chirurgie ist eine Grundvoraussetzung für sichere und effektive Patientenversorgung. Ziel der vorliegenden Studie war die Darstellung von Gemeinsamkeiten und Unterschieden in der Weiterbildung für Plastische Chirurgie innerhalb von Europa.Materialien und Methoden Ein internetbasierter Fragebogen wurde mit Hilfe eines kostenlosen Formularerstellungstools erstellt und verteilt. Die Fragen betrafen Kernpunkte der Weiterbildung für Plastische Chirurgie in Europa. Die Teilnehmer wurden direkt über das European Leadership Forum (ELF) der European Society of Plastic, Reconstructive and Aesthetic Surgery (ESPRAS) kontaktiert. Alle Teilnehmer hatten weitreichende Kenntnisse über die Organisation und Struktur der plastisch-chirurgischen Weiterbildung in ihrem jeweiligen Land.Ergebnisse 29 Teilnehmer*innen aus 23 europäischen Ländern nahmen an der Umfrage teil. Die Weiterbildung für Plastische Chirurgie beinhaltet grundlegende Prinzipien und Techniken zur Wiederherstellung von Form und Funktion innerhalb der verschiedenen Säulen der Plastischen Chirurgie, sowie in allen Körperregionen. In den meisten europäischen Ländern ist eine Rotation in der Intensiv- und Notfallmedizin und die Behandlung kritisch kranker Patienten obligatorisch. Voraussetzung für die Facharztbezeichnung ist die mehrjährige, national organisierte Weiterbildung, der Nachweis einer festgelegten Anzahl selbstständig durchgeführter Operationen, sowie die mündliche und/oder schriftliche Abschlussprüfung.Schlussfolgerung Fachärzte für Plastische und Ästhetische Chirurgie sind hochqualifiziert und auch im Umgang mit Komplikationen geschult. Der Standard der Weiterbildung der europäischen Plastischen Chirurgen ist hoch, so dass innerhalb Europas eine hohe Qualität plastisch-chirurgischer Versorgung gewährleistet ist.
Keywords: ESPRAS; Training; Specialization; Reconstructive Surgery; Aesthetic Surgery; Europe